A Preferential Attachment Model for Tree Construction in P2P Video Streaming - Miranda, Marcio N.; Figueiredo, Daniel R. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2009: Anais do VIII Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2009)
Tree-based peer-to-peer (P2P) video streaming systems rely on a video dissemination tree to deliver video to peers. In order to offer good quality of service, two fundamental aspects should guide the construction of the video dissemination tree: low node degree and short distances to the server. In this paper, we propose a very simple growth process to construct the video dissemination tree. Our generative model is based on the preferential attachment principle, where preference is given in terms of node quality. The proposed model has a single parameter to weigh the relative importance of node degree and node distance on assessing node quality. We investigate our model through simulations and find that surprisingly good video dissemination trees are usually generated. In particular, topological properties of generated trees are never extreme and average tree quality is mostly comparable (and sometimes superior) to carefully designed dissemination trees. Our results indicate that the proposed model is capable of self-organizing nodes into good trees under various assessments of node quality.